Status quo of the public's knowledge of probiotics based on video-sharing platforms - Chun-Hui Jiang; Jia-Jia Xu; Chao Xu; Shi-Yue Chen; Jia-Yun Chen; Jing-Song Xia; Zhuan Liao; Wen-Bin Zou; Xue Fang (BMC, 2023)
Abstract Background Probiotics have been deemed multipotent and unprecedentedly applied in the health field recently. However, there are challenges in promoting credible and reliable resources while avoiding misinformation regarding probiotics for the public. Methods This study analysed 400 eligible probiotic-related videos selected from YouTube, and the three most popular video-sharing platforms (Bilibili, Weibo and TikTok) in China. Video retrieval was performed on September 5th, 2022. GQS and tailored DISCERN tool assess each video's quality, usage, and reliability. A comparative analysis of videos from different sources was carried out. Results The identity distribution of probiotic video-producers was predominantly experts (n = 202, 50.50%), followed by amateurs (n = 161, 40.25%) and health-related institutions (n = 37, 9.25%). The videos' content category mainly discussed the function of probiotics (n = 120, 30%), the way to choose suitable products (n = 81, 20.25%), and the methods for taking probiotics (n = 71, 17.75%).The overall quality of videos was moderate (3/5 point) assessed by GQS, while the usage (1/6 point) and reliability (2/5 point) detailing probiotics assessed by tailored DISCERN tool were poor. The attitude of probiotic video-producers was primarily positive (n = 323, 80.75%), followed by neutral (n = 52, 13.00%) and negative (n = 25, 6.25%) (P < 0.001). Conclusions The current study showed that videos on social media platforms publicise important information including the concepts, usage, and precautions of probiotics to the public. But the overall quality of uploaded videos about probiotics was unsatisfactory. More efforts are needed to improve the higher-quality content of probiotic-related online videos and better propagate probiotic knowledge to the public in the future.